The Effects of Maternal Smoking on Pregnancy and Offspring: Possible Role for EGF? - Janbazacyabar, Hamed; van Daal, Marthe; Leusink-Muis, Thea; van Ark, Ingrid; Garssen, Johan; Folkerts, Gert; van Bergenhenegouwen, Jeroen; Braber, Saskia (Frontiers in Cell and Developmental Biology, 2021)
Cigarette smoke exposure during pregnancy and lactation is associated with adverse pregnancy outcomes. Here, we investigated the effects of maternal smoke exposure on pregnancy and offspring immunity and explored whether, epidermal growth factor (EGF), an important growth-promoting factor in human colostrum and milk, might be a possible missing link in maternal smoke exposure and changes in infants’ immune responses. Pregnant BALB/c mice were exposed to either cigarette smoke or air during gestation and lactation, and effects on pulmonary inflammation in dams and immune responses in offspring were examined. Maternal smoke exposure increased airway hyperresponsiveness and accumulation of inflammatory cells in the lungs of pregnant dams compared to non-pregnant dams. The E-cadherin protein expression was reduced in mammary glands of cigarette smoke-exposed pregnant dams. EGF levels were higher in mammary glands and serum of smoke-exposed pregnant dams compared to air-exposed pregnant dams. Offspring from cigarette smoke-exposed dams exhibited elevated levels of IL-17A, MCP-1, IL-22 and IL-13 in anti-CD3 stimulated spleen cell culture supernatants. EGF levels were also increased in serum of offspring from smoke-exposed dams. A positive correlation was observed between serum EGF levels and neutrophil numbers in bronchoalveolar lavage fluid of the dams. Interestingly, IL-17A, MCP-1, IL-22, IL13 and IFN-γ levels in anti-CD3 stimulated spleen cell culture supernatants of male pups also showed a positive correlation with EGF serum levels. In summary, our results reveal that maternal smoke exposure predisposes dams to exacerbated airway inflammation and offspring to exacerbated immune responses and both phenomena are associated with elevated EGF concentrations.